THE ISSUES WHICH ARE FACED BY STUDENTS WITHIN THE PROCESS OF LEARNING A FOREIGN LANGUAGE AND THEIR SOLUTIONS TO IT - Abdusaidova Gulkhayo Bahriddin kizi (European Science Publishing, 2024)
Learning a foreign language such as English is essential in numerous fields, but it presents challenges for students. One of the difficulties includes the inability to comprehend native speakers while listening. To overcome this issue, students should concentrate on key words rather than every word. Moreover, students struggle with memorizing vocabulary, inhibiting their speaking skills. They can overcome this obstacle by memorizing new words using songs or short videos. Another challenging task is speaking ideas in English fluently, producing pauses and hesitations. However, expressing ideas is the best way to enhance speaking abilities. Pronunciation is another noteworthy problem for learners, and listening to music and singing can be a helpful approach. Lastly, variations in English, such as using formal versus informal language, can be challenging for students. They should conduct research to determine whether certain phrases or idioms are appropriate for specific situations before using them.
Keywords: Learning, foreign language, English, education, science, IT, challenges, listening, meaning, key words, vocabulary, speaking, pauses, pronunciation, native speakers, subtleties, variations, formal, informal, idioms, slangs, research.